1993
DOI: 10.3109/00365529309090255
|View full text |Cite
|
Sign up to set email alerts
|

The Enkephalinase Inhibitor, Acetorphan, in Acute Diarrhoea: A Double-Blind, Controlled Clinical Trial versus Loperamide

Abstract: The antidiarrhoeal properties of acetorphan, an inhibitor of enkephalinase (EC 3.4.24.11) that prevents endogenous enkephalin degradation, and loperamide, a mu opiate receptor agonist, were compared. The double-blind study included 69 patients with acute diarrhoea of presumed infectious origin, allocated at random to two parallel groups. Acetorphan and loperamide were both rapidly and similarly effective, diarrhoea resolving in both cases in nearly 2 days. With acetorphan, however, abdominal distension vanishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 14 publications
5
31
0
1
Order By: Relevance
“…In agreement with another study [34], we found that in racecadotril treatment, abdominal distension vanished rapidly, and reactive constipation was less frequent with respect to the loperamide group. These differences can be accounted for by the distinct mechanisms of antidiarrheal activity of the two drugs as above described.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with another study [34], we found that in racecadotril treatment, abdominal distension vanished rapidly, and reactive constipation was less frequent with respect to the loperamide group. These differences can be accounted for by the distinct mechanisms of antidiarrheal activity of the two drugs as above described.…”
Section: Discussionsupporting
confidence: 93%
“…Hamza et al [32] and Vetel et al [33] reported that racecadotril produced a significant (P=0.025) decrease in stool weight during the first day of treatment compared with placebo and was also associated with significantly fewer diarrheic stools than placebo after 1 day of treatment. Other studies in adult patients reported that racecadotril was able to reduce diarrhea in about 19 h [27,34]. In agreement with these studies, we documented that racecadotril reduced diarrhea in all patients in about 1 day in all episodes of gastroenteritis.…”
Section: Discussionsupporting
confidence: 92%
“…It was concluded that racecadotril is more safe and tolerable than loperamide and is effective in resolving the symptoms associated with diarrhoea. Similar results were reported in other studies by Roge et al, 29 Prado et al 30 and Wang et al 25 …”
Section: Discussionsupporting
confidence: 92%
“…Most modern antidiarrhoeal agents are beyond the reach of the common man in developing countries. In addition, they have some levels of toxic effect [4,5]. To overcome the menace of diarrhoeal disease in developing countries, the World Health Organization (WHO) has included a programme for the control of diarrhoea, which involves the use of traditional herbal medicine [6].…”
Section: Methodsmentioning
confidence: 99%